2019
DOI: 10.1161/circresaha.119.315248
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Autophagy in CD11b + Dendritic Cells Expands CD4 + Regulatory T Cells and Limits Atherosclerosis in Mice

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…For example, CD103 + DCs selectively carry apoptotic intestinal epithelial cells to mesenteric lymph nodes, which function as critical determinants to induce tolerogenic CD4 + regulatory T-cell differentiation in mice [161]. CD11b + DCs with dysfunctional autophagy due to Atg16l1 deficiency expand aortic CD4 + Treg cells and inhibit atherogenesis in Ldlr −/− mice [162]. Indoleamine 2,3-dioxygenase 1 (IDO1)-expressing and chemokine (C-C motif) receptor 9 (CCR9)-positive plasmacytoid dendritic cells (pDCs) in the aorta locally induce aortic Treg cells, which produce IL-10 and subsequently prevent atherogenesis in mice [163].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…For example, CD103 + DCs selectively carry apoptotic intestinal epithelial cells to mesenteric lymph nodes, which function as critical determinants to induce tolerogenic CD4 + regulatory T-cell differentiation in mice [161]. CD11b + DCs with dysfunctional autophagy due to Atg16l1 deficiency expand aortic CD4 + Treg cells and inhibit atherogenesis in Ldlr −/− mice [162]. Indoleamine 2,3-dioxygenase 1 (IDO1)-expressing and chemokine (C-C motif) receptor 9 (CCR9)-positive plasmacytoid dendritic cells (pDCs) in the aorta locally induce aortic Treg cells, which produce IL-10 and subsequently prevent atherogenesis in mice [163].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Dendritic cells (DCs) are professional APCs found in atherosclerotic plaques [ 167 ]. The contribution of DCs in atherogenesis is exerted through their role in lipid metabolism and in modulation of T reg responses and T-cell activation [ 168 , 169 , 170 ]. Albeit dispensable for DC development, autophagy contributes to DC function and affects a range of processes, including maturation, migration, cytokine production, migration, and T-cell activation [ 171 ].…”
Section: Role Of Autophagy In Different Cell Typesmentioning
confidence: 99%
“…Albeit dispensable for DC development, autophagy contributes to DC function and affects a range of processes, including maturation, migration, cytokine production, migration, and T-cell activation [ 171 ]. The autophagic flux is activated in DCs during atherogenesis and disruption of autophagy in DCs (in Cd11c Cre+ Atg16l1 flox/flox mice) elicits an immunosuppressive response, promotes the expansion of T reg cells, and limits atherosclerosis [ 170 ]. Given the relevance of autophagy in regulating functional properties of DCs, and their impact in innate and adaptive immune response, targeting autophagic pathways in specific DC subsets may provide insights into their plasticity and potential therapeutic chances in atherosclerosis.…”
Section: Role Of Autophagy In Different Cell Typesmentioning
confidence: 99%
“…Autophagy has recently emerged as a major modulator of a variety of cellular functions with high relevance to the development and progression of atherosclerosis ( 61 ). A recent study revealed that CD11b + DC deficient in an autophagy-related molecule Atg16L that binds ATG5 and links the isolation membrane to the formation of the autophagosome ( 62 ), developed a TGF-b-dependent tolerogenic phenotype and promoted the expansion of Tregs, whereas no such effects were seen with Atg16l1 deficient CD8a + DCs ( 63 ), suggesting an essential role of Atg16L complex in the suppressive function of CD11b + DCs via autophagy. Consistently, the expanded aortic Tregs in vivo , limited accumulation of Th1, and reduced development of atherosclerosis in CD11c Cre − Atg16l1 flox / flox Ldlr −/− mice ( Atg16l1 deletion in total DCs) were proven to be caused by CD11b + DC subset, as no such effects were seen when Atg16l1 was deleted selectively in conventional CD8a + DCs and CD103 + DCs ( 63 ).…”
Section: Roles Of Different Subsets Of Vascular Dendritic Cells In Atmentioning
confidence: 99%